INTEGRASI TERBATAS TEOLOGI DAN PSIKOLOGI:: ANALISIS FUNGSIONAL DAN ONTOLOGIS DALAM WACANA KONSELING PASTORAL - Yosep Belay (STT-RAI Batam, 2026)
The discourse on the integration of theology and psychology in the context of pastoral counseling remains a contentious issue within the evangelical tradition. Some theologians and pastoral practitioners endorse an integrative approach with adjustments to certain components, while others reject such integration efforts due to concerns about potential distortions of Christian faith, morality, and worldview. This article is situated within the framework of integrative thought, with several theoretical considerations that the author assumes may be beneficial for pastoral ministry, particularly in the field of counseling. The nature of this research draws on theoretical discourse grounded in grounded theory, thus employing conceptual and integrative analysis through a literature review. The research data draws on primary and secondary references from academically representative experts. While the results of this study indicate that efforts toward an integrative approach between theology and psychology remain open for exploration, they are currently limited to comparative studies regarding the use of information, diagnostic findings, and therapeutic methods in psychology that align with a biblical approach for the application of pastoral counseling. However, certain fundamental aspects—such as worldview, philosophy, and methods within the realm of modern psychology—cannot be integrated